The impact of the c.5603A>T hypomorphic variant on founder mutation screening of ABCA4 for Stargardt disease in South Africa - Midgley, Nicole (Mol Vis, 2020)
PURPOSE: Seven founder mutations in ABCA4 underlie a large proportion of Stargardt disease in the South African Caucasian population of Afrikaner descent. The Quick 7 assay was locally developed to test for these specific mutations and is available through the National Health Laboratory Service. However, in 2017 it was suggested that one of these mutations, c.2588G>C (p.Gly863Ala), is only pathogenic when present in cis with the c.5603A>T (p.Asn1868Ile) hypomorphic variant. Several patients and family members have been screened and have had their results delivered; thus, a retrospective analysis for the presence of c.5603A>T in all resolved ABCA4 cases was warranted. METHODS: In this study, probands with biallelic mutations in ABCA4 and all families carrying the c.2588G>C variant were genotyped for c.5603A>T with restriction fragment length polymorphism analysis. Cosegregation analysis was performed to ascertain the phase of causative mutations. RESULTS: The downgraded c.2588G>C variant was present in 26 families, of whom 24 (92.31%) also carried the hypomorphic variant (cis phase confirmation was possible in 12 families). Two families (7.69%) carried the downgraded variant without the hypomorphic variant; however, in these cases the second disease-causing variant had not been identified. These two families remained in research mode; therefore, family follow-up was not immediately required. Additionally, the hypomorphic variant occurred in cis with two of the other Quick 7 mutations. CONCLUSIONS: This study adds to the evidence of the pathogenicity downgrade of c.2588G>C, as it results in disease when in cis with c.5603A>T in this cohort. This work highlights the value of a close link between research and diagnostic laboratories, in keeping abreast of the functionality of variants. It is recommended that the Quick 7 assay be expanded to include c.5603A>T, and that only the complex c.[2588G>C;5603A>T] allele be reported as pathogenic. Confirmation of cis or trans configuration of alleles by the inclusion of familial samples is strongly recommended.